2012
DOI: 10.1002/pmic.201100389
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of aquaporins, small GTPases and VATPases proteins in rice leaves subjected to drought stress and recovery

Abstract: Mechanisms of drought tolerance are complex, interacting, and polygenic. This paper describes patterns of gene expression at precise physiological stages of drought in 35-day-old seedlings of Oryza sativa cv. Nipponbare. Drought was imposed gradually for up to 15 days, causing abscisic acid levels to rise and growth to cease, and plants were then re-watered. Proteins were identified from leaf samples after moderate drought, extreme drought, and 3 and 6 days of re-watering. Label-free quantitative shotgun prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 55 publications
1
68
0
Order By: Relevance
“…WRKY33, have been reported to participate in many ABA-related responses, including the activation of ROS detoxification processes [71]. Moreover, the induction of several genes coding for RESPONSIVE TO DESSICATION 29B and for various types of small GTP-binding proteins in water stressed and/ or recovered AhNF-YC OE plants was in agreement with the critical function of these proteins in ABA membrane perception and/ or down-stream signaling events during abiotic stress signaling [72][73][74]. Additional support for a largely ABA-dependent participation in water stress resistance was the predominant down-regulated expression of several genes coding for ERD proteins, which are generally induced as part of the ABA-independent stress responses, in water-stressed and recovered plants.…”
Section: Discussionmentioning
confidence: 58%
“…WRKY33, have been reported to participate in many ABA-related responses, including the activation of ROS detoxification processes [71]. Moreover, the induction of several genes coding for RESPONSIVE TO DESSICATION 29B and for various types of small GTP-binding proteins in water stressed and/ or recovered AhNF-YC OE plants was in agreement with the critical function of these proteins in ABA membrane perception and/ or down-stream signaling events during abiotic stress signaling [72][73][74]. Additional support for a largely ABA-dependent participation in water stress resistance was the predominant down-regulated expression of several genes coding for ERD proteins, which are generally induced as part of the ABA-independent stress responses, in water-stressed and recovered plants.…”
Section: Discussionmentioning
confidence: 58%
“…GTP-binding genes play a crucial role in a number of cellular processes in plants, such as vesicle-mediated trafficking, signal transduction, and cell division. Differential expression of these genes has previously been reported in plants under abiotic stress conditions (Mirzaei et al 2012). Oxidation-reduction process is essential to maintain cellular homeostasis via generation of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…For drought, label-free quantitative shotgun proteomics showed that there was a differential regulation of aquaporins. Similarly, proteins involved in signalling and transport showed differential regulation, suggesting a critical role in the overall response to drought (Mirzaei et al 2012 ). These studies are just but few from among the many research highlights.…”
Section: Rice and Wheatmentioning
confidence: 97%